Where science meets practice: Olympic coaches` crafting of the tapering process? - Ritchie, D.; Allen, J. B.; Kirkland, A. (Journal of Sports Sciences, 2018)
Although there is research providing physiologically-based guidance for the content of the taper, this study was the first to examine how coaches actually implement the taper. The purpose of this study was to examine the taper planning and implementation processes of successful Olympic coaches leading up to major competitions and how they learned about tapering. Seven track and field coaches participated in semi-structured interviews exploring their tapering processes. To be considered for inclusion, coaches were required to have coached one or more athletes to an Olympic or Paralympic medal. Through a process of axial and open coding interview transcripts were analysed and lower and higher order themes developed describing the coaches` tapering processes. Our findings indicate that the strategies employed to achieve the desired physiological adaptions of the taper were consistent with research (e.g., reduction in volume whilst maintaining intensity and frequency). However, our findings also suggest that tapering is far from a straight forward "textbook" process. The taper was not restricted to physiological outcomes with coaches considering athletes` psychological as well as physical state. Coaches also involved the athlete in the process, adapted the taper to the athlete, continually monitored its progress, and adapted it further as required.